Making Sense of Sentencing - Roberts, Julian V.; Cole, David, 1948- (Book collections on Project MUSE., 1999)
On 3 September 1996, Bill C-41 was proclaimed in force, initiating one significant step in the reform of sentencing and parole in Canada. This is the first book that, in addition to providing an overview of the law, effectively presents a sociological analysis of the legal reforms and their ramifications in this controversial area.The commissioned essays in this collection cover such crucial issues as options and alternatives in sentencing, patterns revealed by recent statistics, sentencing of minority groups, Bill C-41 and its effects, conditional sentencing, and the structure and relationship between parole and sentencing are clearly presented. An introduction, editorial comments beginning each chapter, and a concluding chapter draw the essays together resulting in a timely, comprehensive and extremely readable work on this critical topic.Broad in scope and perspective, this major new socio-legal study of the law of sentencing will be illuminating to students, members of the legal profession, and the general reader.